Demonstration of simultaneous experiments using thin crystal multiplexing at the Linac Coherent Light Source. (9th April 2015) - Feng, Y.; Alonso‐Mori, R.; Barends, T. R. M.; Blank, V. D.; Botha, S.; Chollet, M.; Damiani, D. S.; Doak, R. B.; Glownia, J. M.; Koglin, J. M.; Lemke, H. T.; Messerschmidt, M.; et al.
<x xml:space="preserve">Abstract</x> Multiplexing of the Linac Coherent Light Source beam was demonstrated for hard X‐rays by spectral division using a near‐perfect diamond thin‐crystal monochromator operating in the Bragg geometry. The wavefront and coherence properties of both the reflected and transmitted beams were well preserved, thus allowing simultaneous measurements at two separate instruments. In this report, the structure determination of a prototypical protein was performed using serial femtosecond crystallography simultaneously with a femtosecond time‐resolved XANES studies of photoexcited spin transition dynamics in an iron spin‐crossover system. The results of both experiments using the multiplexed beams are similar to those obtained separately, using a dedicated beam, with no significant differences in quality.